The Supply Chain Resources in Job Performance on Hospitality and Tourism Sector - NORMI, Siti (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020DO - 10.14505//jemt.v11.2(42).21, 2020)
Using 110 respondent’s hospitality and tourism service employees as the sample in Berastagi hospitality and tourism area in Karo Regency, North Sumatera. Data which is obtained were analyzed by using “analysis of the path”. The result of research is: the impact direct of discipline and significant on job satisfaction, discipline has an the impact direct on job performance, job promotion has an the impact direct on job performance, job satisfaction has an the impact direct on job performance, discipline has an the impact direct on job performance without through job satisfaction, and job promotion not has an the impact direct on job performance through job satisfaction, and job promotion not has an the impact direct on job performance through job satisfaction  for hospitality and tourism service employees in Berastagi hospitality and tourism area in Karo Regency, North Sumatera.